Powerplan : The alternative software for presentations at local area network using virtualtreeview and omnithread - Daniel Silli Bataona; Rinaldi Munir; Tutun Juhana; Gloria Christiana Manulangga; Jemsrado Sine (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The need for LCD projectors is very urgent, so even though they often experience shortcomings, it is impossible to continue to make purchases when needed to repair LCD projectors that require high costs such as buying a new device. Software development from the results of this study is not only beneficial for educational institutions but also for personal or specific institutions and institutions who want to conduct seminars, presentations, or other activities that involve many audiences. The advantage is that the audience will not experience problems such as when using an LCD projector, such as limited visibility, location or space, and the viewpoint of the audience on the Projector LCD / Screen. Another contribution that can be given from this research is a model of the teaching and learning process in real-time without using an LCD and only using a PC/ Laptop connected to the same LAN. It is a development of research that supports the concept of green computing because it also reduces the use of equipment LCD projector, but the usage function remains the same even more effective and interactive even without the device. Presentation model like this is the development of new models in the learning process using LAN networks but without using the internet connection and is the cross-platform model. This research can be the answer to the need for using LCD projectors that often occur in the process of education, meetings, or seminars that continue to increase every time. Also, the lack of LCD compared to the number of teaching needs in each class and the unstable electricity conditions and the low electricity ratio in East Nusa Tenggara, have resulted in frequent blackouts suddenly, so that makes the device LCD vulnerable to damage. The test results showed an increase in RTT along with the increasing number of servers conducting presentation activities. Testing on LAN networks with the same number of clients on each test shows that there was an increase of 18% and 75% in each addition to the number of servers. The best performance of Powerplan is still shown when the number of servers that present several five, with the response time of each client connected under two seconds.